Grammatical Evidence Outside the Period of Linguistic Authority: Bashar ibn Burd as a Model - allouani, abdou; laouidji, ahmed (El Omda in Linguistics and Discourse Analysis, 2023)
This topic is primarily based on examining grammatical evidence outside the period of linguistic authority (ḥujjah), that is, after the end of the linguistic timeframe defined by early Arab scholars. Classical Arab grammarians relied on the poetry of the first and second poetic generations as valid linguistic evidence, while excluding later poets and muḥdathūn due to the spread of linguistic errors in their speech. However, some later poets achieved a high level of eloquence and linguistic mastery, even if their chronological position prevented them from being accepted as authoritative evidence. This raises the question: did these poets receive any recognition from early grammarians, and is it objectively justified to exclude them entirely from the domain of grammatical citation and linguistic argumentation?